COMMUNICATION TECHNOLOGY OF ETHNIC CONFLICT-CONFRONTATIONAL INTERACTION'S ESCALATION (BASED ON PERIODICALS IN WESTERN UKRAINE, SUMMER AND AUTUMN, 1941) - Гулай, В. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Approaches to communication technologies distinguish in the paper in the context of communication strategies and tactics of conflict behavior. The author analyzes the OUN periodicals that appeared in eastern Galicia and western Volhynia after its capturing by the forces of Nazi Germany and its allies and subjects of the first print media allowed by occupation administration District "Galicia" and Reichscommisariat "Ukraine" in August 1941. It is determined that manipulative, propagandistic communication technologies played a major role in the escalation of ethnic conflict interaction in Western Ukraine on the initial phase of the Second World War.